Program of self-esteem in the school performance in primary education - Sánchez Figueroa, Nora Helly (2014)
The current research article shows the Influence of a Program of Self-esteem in the School performance applied at students of fourth and fifth grade of Primary Education in the Educational Institution Nº 10039 of the District of New Arica - 2012". The research was carried out through a quasi -experimental design and which had 40 students, with a control and experimental group. Every group with 20 students respectively (4° and 5° grades). This research carried out the phases of the experiment, by implementing the COOPERSMITH test, surveys, and interviews; it allowed to identify the problematic reality referred at the level of self-esteem and how it influences in their school performance, which didn't allow them to develop all their potentialities and cognitive and affective skills, the results were that the students so much for the experimental group as in the group control that possess a low academic performance and this is due to the influence that tends to have a low self-esteem. After having developed the experiment on the basis of the theoretical references used, it was confirmed that the school performance improved its quality. The results indicate the advantageous that is to apply this type of stimulus in an effort to improve the academic performance of students. At conclude, the implemented program, it can be said that self-esteem program contributed successfully on the improvement of performance in each of these students.